Seed Quality as Affected by Mid Cone Diameter in Pinus roxburghii Sargent - Singh, Virendra; Kumar, Shashi (Indian Forester, 2004)
The present investigation was undertaken to find out the effect of mid cone diameter classes on seed quality in Chir pine. The cones were grouped into small (5-<6cm), medium (6-<7cm) and large (7-<8cm) cone diameter classes. The large cones showed superiority in germination percent, germination value, germination capacity, germination energy and germination speed over other cone diameter classes. Also, there existed a positive and highly significant correlation between cone diameter and different seed parameters. Therefore, large cones (in diameter) should be given preference for quality seed collection.